Primary Umbilical Endometriosis (Villar’s Nodule): A Rare Symptomatic Umbilical Pathology in An Adult Woman (KYAMC Journal, 2022)
A 35-year old married non-diabetic, non-hypertensive, non-alcoholic, non-smoking and non-betel-nut-chewing poor housewife having average body build and body weight hailing from Shahjadpur of Sirajgonj district got herself admitted with intermittent pain and 2.5x1.75 cm sized discolored swelling in the umbilical region for one year. The dull aching non-radiating pain aggravated by moving was not associated with fever, chills and rigor. The pain was distinctly remarkable during regular normal menstrual flow. It was responding variably to traditional analgesic and nonspecific antimicrobial drugs as advised by local village doctors. But she was not cured. Her bowel and bladder habits were normal. She had no abdominal pain, distension, chest pain, bone pain, dyspnea, cough, jaundice, umbilical discharge of faeces, blood or urine. Her two children were born normally (i.e., by NVD: Normal Vaginal Delivery). She had no previous history of any form of surgery. Her rt-PCR for Covid-19 test was negative with normal liver and kidney function tests and normal sonographic findings of the whole abdomen. Our clinical diagnosis of primary umbilical endometriosis was supported by FNAC from discolored umbilical swelling. After having an informed written consent we excised the umbilicus. The histopathological report had confirmed our preoperative diagnosis. The post-operative period was smooth and uneventful. We like to share our experience of diagnosing and treating this very rare disease of primary umbilical endometriosis.KYAMC Journal Vol. 13, No. 01, April 2022: 56-60